Red blood cell segmentation using masking and watershed algorithm: A preliminary study - Johan, Mohamad Sharif; M. F., Miswan; Md Asri, Ngadi; Md Sah, Hj Salam; Muhammad Mahadi, Abdul Jamil (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/